Simetria cervical e suas relações com lado de preferência mastigatório em crianças com respiração oral secundária à rinite alérgica - BEZERRA, Luciana Ângelo (2014)
Allergic rhinitis is characterized by nasal mucosa inflammation mediated by Eimmunoglobulin and presents as main symptoms and signs: nasal itching , sneezing, rhinorrhea aqueous, nasal obstruction and, in some cases, mouth breathing. Mouth breathing usually leads to craniofacial (changing stomatognathic system functions, whose main one is mastication), musculoskeletal and body axis (forward head) changes. This study objective was to verify the relationship between cervical symmetry with masticatory preference side in children with mouth breathing secondary to allergic rhinitis. It’s a transversal study, controlcase type, with two children groups from 4 to 12 incomplete years old, with mouth breathing secondary to allergic rhinitis (GRA) and another group without mouth breathing neither allergic rhinitis (CG). The children and their parents answered a questionnaire (personal data, sociodemographic, child sleep quality, assessment of mouth breathing and ISAAC - International Study of Asthma and Allergies in Childhood). The physical assessment were comprised by neck region goniometry, facial pachymetry, dental arch (complete or incomplete). Subsequently, the child remained in standing posture, being points marked on her body and recorded three photographs in each view (anterior, right and left profile, and posterior). Then, it was performed mastication assessment in which the child was comfortably seated, and was instructed to eat a 25g french bread, in front of the same film machine and the time was recorded. For posture, the photographs were evaluated by SAPO® software and were characterized in forward, posteriorized or normal head position (right profile); and, in normal, right or left tilted (anterior view). The masticatory function was assessed by film observing, with the masticatory cycles counting and being categorized into normal mastication, preferably mastication to the right or left side, simultaneous bilateral mastication, unilateral right or left exclusively. It was analyzed 94 children in GRA and 45 in GC, these 6 children from GRA were excluded two for refusing to eat the bread, two for not being able to eat the bread and two for not presenting enough scored to be classified as an individual with oral breathing. It was observed a greater likelihood of children with allergic rhinitis experiencing snoring (OR 2.21, IC 95% 1.06 – 4.59) and night hypersialorry (OR 3.33, IC 95% 1.56 – 7.09). It was observed that 73/88 (82.95%) children of GRA and 38/45 (84.44%) of GC had forward head; 41/88 (46.60%) of the GRA and 31/45 (68.89%) of the GC had left head tilt. Regarding to mastication we found a higher percentage of normal masticatory type, in both groups, but it was observed high speed masticatory, high amount of chewing cycles. When was associate masticatory function to postural changes at GRA we found 25/88 (28.40%) of GRA children with forward head and mastication changes and 15/88 (17.04%) with left tilt head with mastication changes, but did not observe any statistically significant difference (p=0.19 and p=0.35 respectively). But it was seen clinically important changes that affect the children functional performance. It is recommend future studies with larger sample because there are small subgroups formation from the masticatory and postural assessment.